2015
DOI: 10.1002/pen.24090
|View full text |Cite
|
Sign up to set email alerts
|

Rheological behavior of uncured styrene-butadiene rubber at low temperatures, pure and filled with carbon black

Abstract: International audienceThe flow behavior of an uncured styrene-butadiene rubber (SBR) has been studied by using a specific preshearing capillary rheometer in the range of temperatures encountered in extrusion, i.e. between 40°C and 90°C. A pure SBR and various SBR compounds filled with different amounts of carbon black (from 17 to 33 wt%) have been characterized. It was observed, for all tested materials, that the flow curve could be divided in different parts: at low shear rate, the material exhibits a classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
4
8
0
Order By: Relevance
“…47,48 Note that we relate our values of E a to the viscous dissipation of the PF-GO composite and not the thermooxidative processes and hemolytic dissociation of crosslinked bridges between PF and GO as reported otherwise. 49 Comparing the rheological response of our PF/m-GO samples to petroleumbased elastomers, such as styrene-butadiene rubbers and hyperbranched polyisoprene, our values of G 0 over the corresponding unshied frequency range and h are found in a good agreement to the studies, 47,50,51 reporting shear thinning behavior and strong elastic response as shown in Fig. 6.…”
Section: Runsupporting
confidence: 84%
“…47,48 Note that we relate our values of E a to the viscous dissipation of the PF-GO composite and not the thermooxidative processes and hemolytic dissociation of crosslinked bridges between PF and GO as reported otherwise. 49 Comparing the rheological response of our PF/m-GO samples to petroleumbased elastomers, such as styrene-butadiene rubbers and hyperbranched polyisoprene, our values of G 0 over the corresponding unshied frequency range and h are found in a good agreement to the studies, 47,50,51 reporting shear thinning behavior and strong elastic response as shown in Fig. 6.…”
Section: Runsupporting
confidence: 84%
“…One hundred twelve phr corresponds to 38 wt% (weight percent), but mainly the properties of the polymer define the onset of the plateau, as all the samples lead to a plateau starting at a similar shear rate as the unfilled SBR. Only higher-filled compounds above 30 phr show a second branch after the plateau in accordance with Crié et al (2015).…”
Section: Discussionsupporting
confidence: 59%
“…Figures 3, 4, and 5 show that the apparent shear rates ̇𝛾p at which the change of slope appears are independent of the silica loadings but shifts with temperature. Crié et al (Crié et al 2015) showed that a master curve can be constructed from the individual flow curves of carbon-filled SBR compounds. Mongruel and Cartault (Mongruel & Cartault 2006) determined a so-called concentration shift factor which allows the construction of a master curve representation for the elastic moduli of silica and carbon black-filled SBR compounds.…”
Section: Master Curvesmentioning
confidence: 99%
“…In addition to the rubber structure, [19][20][21][22] the characteristics, content and introduction method of the ingredients (curing system, llers, plasticizers, etc. ), [23][24][25][26][27][28] as integral parts of rubber composites, play a signicant role in determining the rheological behaviors of the composites. For example, Patcharaphun et al 23 concluded that the viscosity of rubber compounds utilizing conventional and efficient vulcanizing systems was lower than that of compounds with nonsulfur systems at any given shearing rate.…”
Section: Introductionmentioning
confidence: 99%